2010
DOI: 10.4316/aece.2010.04022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic shielding of the magnetic fields

Abstract: The paper presents a comparative study of the methods used to control and compensate the direct and alternative magnetic fields. Two frequently used methods in the electromagnetic compatibility of the complex biomagnetism installations were analyzed. The two methods refer to the use of inductive magnetic field sensors (only for alternative fields) and of fluxgate magnetometers as active transducers which measures both the direct and alternative components of the magnetic field. The applications of the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The first winding is used for the manual compensation of the continuous component of the vector magnetic field along the three directions (X, Y, Z) within the range ±40 A/m. The second winding serves to compensate the alternating and slowly variable components of the magnetic field within the range ±40 A/m, making use of a system controlled by a triaxial magnetometer which operates in the negative feedback loop [31], [32].…”
Section: Methodsmentioning
confidence: 99%
“…The first winding is used for the manual compensation of the continuous component of the vector magnetic field along the three directions (X, Y, Z) within the range ±40 A/m. The second winding serves to compensate the alternating and slowly variable components of the magnetic field within the range ±40 A/m, making use of a system controlled by a triaxial magnetometer which operates in the negative feedback loop [31], [32].…”
Section: Methodsmentioning
confidence: 99%
“…The magnetic fields have been already used in diagnostics in connection with eminent sources of the fields, such as electrical energy converters and transformers, as well as furnaces with induction heating [37]. These measurements were performed for the purpose of the occupational hygiene [38][39][40] or compatibility issues [41][42][43][44]; they were mostly realized on static devices or near electric motors in case of mobile systems.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Several studies have identified the effect of electromagnetic interference on image resolution and proposed solutions to minimize its effect. [6][7][8][9][10]11 The causes and solutions for the image distortions due to sample drift are discussed in. 6,10,[12][13][14][15][16][17] Image distortions due to vibrations are seen at atomic resolution.…”
Section: Introductionmentioning
confidence: 99%